Competências socioemocionais nos serviços de Saúde Pública: um estudo com gerentes de Centros de Saúde da Família - Sá, Taísa Freire Mororó de (2023)
This study aimed to evaluate the level of socio-emotional skills of managers of family health centers in the city of Sobral - CE. This is an exploratory, descriptive and cross-sectional study, with a quantitative approach. The scenario was primary health care in Sobral, specifically the family health centers. The participants were the managers of twenty-eight health centers, based on the inclusion criteria: being a health center manager for at least one year and being in the operating scenario at the time of the evaluation. The study was developed using a survey- type form, applied in the months of June and July 2023, through Google forms, containing a socio-biodemographic questionnaire and the Macedo e Silva socio-emotional skills scale (2020); The data collected in the form were entered into Excel, analyzed using simple statistics and presented through tables and graphs, making it possible to outline the profile and level of socio-emotional skills. 18 managers participated, equivalent to 64% of Sobral's managers, of which all are nurses and 94.40% have lato sensu specialization. Females accounted for 94.40%; the most frequent age group was 30 to 39 years old (55.60%), the average age was 36.1. Regarding the time working in an eSF, 50% have between 5 and 10 years of experience, but in relation to the time as manager at the Sobral health center (50%), they have less than 2 years. Managers presented high scores, that is, they represent high levels of skills in all five dimensions of skills assessed by the Macedo and Silva scale: emotional awareness (73.14) - emotional balance (72.5) - teamwork (83. 5) - self-control (75) - emotional creativity (76.6). The teamwork dimension was the most powerful, while emotional balance and emotional awareness represented lower values. According to the literature, high levels of skills indicate managers who are more efficient at work, produce more, have more autonomy and are more decisive, in addition to being seen as examples for the team. High skills can promote professional satisfaction. Finally, it is understood that the objective of this study was not focused on evaluating the satisfaction of managers, relationships with teams and their productivity, therefore, new analyzes are suggested to verify the professional satisfaction of these managers who presented high levels of skills. It is also clear that socio- emotional skills are necessary for health management, however, studies are still few and the scopes are still small, like this study.